2023
DOI: 10.1021/acs.est.2c08110
|View full text |Cite
|
Sign up to set email alerts
|

Nonphthalate Plasticizers in House Dust from Multiple Countries: An Increasing Threat to Humans

Abstract: Along with the restrictions of phthalate esters (PAEs), a variety of nonphthalate plasticizers (NPPs) have been increasingly used for industrial needs. Knowledge remains limited on the environmental occurrences, fate, and human exposure risks of many emerging NPPs. In this study, we investigated a suite of 45 NPPs along with the major PAEs in house dust from five regions in the Asia-Pacific region and the United States. The findings clearly demonstrated ubiquitous occurrences of many NPPs in the home environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…This heavy contamination caused by VAs has been previously highly overlooked in our environments before. To our knowledge, among all recorded polymer additive contaminations in house dust from South China, the median concentration of ∑VAs was second only to that of phthalate/nonphthalate plasticizers (252,000−750,000 ng/g) 39,40 but significantly higher than those of synthetic antioxidants (7890 ng/g), 41 organophosphate esters (10,600 ng/g), 42 polybrominated diphenyl ethers (4330 ng/g), 43 and alternative flame retardants (5030 ng/g). 44 These comparisons indicated that serious VA emissions into the environment should be of deep and emerging concern.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…This heavy contamination caused by VAs has been previously highly overlooked in our environments before. To our knowledge, among all recorded polymer additive contaminations in house dust from South China, the median concentration of ∑VAs was second only to that of phthalate/nonphthalate plasticizers (252,000−750,000 ng/g) 39,40 but significantly higher than those of synthetic antioxidants (7890 ng/g), 41 organophosphate esters (10,600 ng/g), 42 polybrominated diphenyl ethers (4330 ng/g), 43 and alternative flame retardants (5030 ng/g). 44 These comparisons indicated that serious VA emissions into the environment should be of deep and emerging concern.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…DEHP has been categorized as a 1B substance under the Global Harmonized System of Classification and Labeling of Chemicals, which means it is a known or suspected carcinogen based on animal evidence . DINCH has been widely adopted as a substitute for phthalate esters in rubber products; however, recent studies have indicated that DINCH can bind to peroxisome proliferator-activated receptor γ and induce adipogenesis. For the TPU shoe sole, the RQ values for UV-234 and AO1024 were 0.02 and 0.01, respectively. Only one chemical (diAMS, 0.08) had an RQ value of >0.01 for the RB shoe sole.…”
Section: Resultsmentioning
confidence: 99%
“…Phthalates are synthetic substances that are widely employed as plasticizers, accounting for up to 40% of the final plastic product 19 and contributing a predicted 18 billion pounds per year. 10,20 Phthalate plasticizers constitute about 80-85% of the global market for use in polyvinyl chloride plastics. 8 Their application is found in a variety of products, including medical devices, food packaging, construction materials, automobile parts, children's toys, and PVC-based goods.…”
Section: Phthalates or Legacy Plasticizersmentioning
confidence: 99%
“…It was projected that these emerging plasticizers would grow to encompass 40% of global plasticizers. 9,10,53 Emerging plasticizers possess intricate chemical compositions, primarily featuring functional groups like benzoate, sebacate, azelate, adipate, terephthalate, trimellitate, citrate, and oleate, to name a few. 10,54,55 In addition to being applied as alternative PVC plasticizers, these compounds are used as solvents and additives in cosmetics, inks, and adhesives.…”
Section: Emerging or Alternative Plasticizersmentioning
confidence: 99%